Aplicación móvil para aprendizaje de lengua Huitoto-Murui en instituciones educativas de nivel inicial del distrito de Punchana - Nuñez Satalaya, Angela Milagros (2020)
The work has been carried out with the participation of students from early education institutions in the urban area of the Punchana district, with the aim of fostering the dissemination, promotion, revitalization and visibility of the indigenous languages and cultures of the Peruvian Amazon from the first pillars of basic education. It also sought to promote the use of technological tools as complementary educational material for the teaching and learning process of basic content in early childhood. The main objective was to study the effects on the learning of the Huitoto-Murui language, based on the use of the "Urue" mobile application in early education institutions in the district of Punchana. The research is of the Applied type, being the design Experimental. The results achieved have been favourable for the class sessions carried out using the mobile application, so it is concluded that the use of a mobile application improves the learning of an indigenous language in educational institutions in the urban area of the Punchana district, in this case the Huitoto-Murui language; therefore, the Hypothesis is accepted: If the mobile application is used, then the learning of the Huitoto-Murui language in early level educational institutions in the Punchana district will be improved.